Mycobacterium leprae Recombinant Antigen Induces High Expression of Multifunction T Lymphocytes and Is Promising as a Specific Vaccine for Leprosy - Bezerra-Santos, Márcio; do Vale-Simon, Marise; Barreto, Aline Silva; Cazzaniga, Rodrigo Anselmo; de Oliveira, Daniela Teles; Barrios, Mônica Rueda; Ferreira, Alex Ricardo; Santos-Bio, Nanci C.; Reed, Steven G.; de Almeida, Roque Pacheco; Corrêa, Cristiane Bani; Duthie, Malcolm S.; et al. (Frontiers in Immunology, 2018)
Leprosy is a chronic disease caused by M. leprae infection that can cause severe neurological complications and physical disabilities. A leprosy-specific vaccine would be an important component within control programs but is still lacking. Given that multifunctional CD4 T cells [i.e., those capable of simultaneously secreting combinations of interferon (IFN)-, interleukin (IL)-2 and tumor necrosis factor (TNF)] have now been implicated in the protective response to several infections, we tested the hypothesis if a recombinant M. leprae antigen-specific multifunctional T cells differed between leprosy patients and their healthy contacts. We used whole blood assays and peripheral blood mononuclear cells to characterize the antigen-specific T cell responses of 39 paucibacillary (PB) and 17 multibacillary (MB) leprosy patients and 31 healthy household contacts (HHC). Cells were incubated with either crude mycobacterial extracts (M. leprae cell sonicate - MLCS) and purified protein derivative (PPD) or recombinant ML2028 protein, the homolog of M. tuberculosis Ag85B. Multiplex assay revealed antigen-specific production of IFN- and IL-2 from cells of HHC and PB, confirming a Th1 bias within these individuals. Multiparameter flow cytometry then revealed that the population of multifunctional ML2028-specific T cells observed in HHC was larger than that observed in PB patients. Taken together, our data suggest that these multifunctional antigen-specific T cells provide a more effective response against M. leprae infection that prevents the development of leprosy. These data further our understanding of M. leprae infection/leprosy and are instructive for vaccine development.